Membrane Mechanical Properties Regulate the Effect of Strain on Spontaneous Electrophysiology in Human iPSC-Derived Neurons. (15th April 2019) - Bianchi, Fabio; Pereno, Valerio; George, Julian H.; Thompson, Mark S.; Ye, Hua
Abstract: Peripheral nerves contain neuron fibers vital for movement and sensation and are subject to continuous elongation and compression during everyday movement. At supraphysiological strains conduction blocks occur, resulting in permanent or temporary loss of function. The mechanisms underpinning these alterations in electrophysiological activity remain unclear; however, there is evidence that both ion channels and network synapses may be affected through cell membrane transmitted strain. The aim of this work was to quantify the changes in spontaneous activity resulting from application of uniaxial strain in a human iPS-derived motor neuron culture model, and to investigate the role of cell membrane mechanical properties during cell straining. Increasing strain in a custom-built cell-stretching device caused a linear decrease in spontaneous activity, and no immediate recovery of activity was observed after strain release. Imaging neuronal membranes with c-Laurdan showed changes to the lipid order in neural membranes during deformation with a decrease in lipid packing. Neural cell membrane stiffness can be modulated by increasing cholesterol content, resulting in reduced stretch-induced decrease of membrane lipid packing and in a reduced decrease in spontaneous activity caused by mechanical strain. Together these results indicate that the mechanism whereby cell injury causes impaired transmission of neural impulses may be governed by the mechanical state of the cell membrane, and contribute to establishing a direct relationship between neural uniaxial straining and loss of spontaneous neural activity. Graphical abstract: Unlabelled Image Highlights: Human iPSC-derived motor neurons were subject to uniaxial strain. Spontaneous activity was measured using calcium imaging. Spontaneous activity decreases with applied strain. Membrane lipid packing (by c-Laurdan imaging) decreases with applied strain. Cholesterol addition to membranes decreases fluidization and reduces loss of activity.